2013
DOI: 10.1016/j.jprot.2013.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Protein isoform-specific validation defines multiple chloride intracellular channel and tropomyosin isoforms as serological biomarkers of ovarian cancer

Abstract: New serological biomarkers for early detection and clinical management of ovarian cancer are urgently needed, and many candidates have been reported. A major challenge frequently encountered when validating candidates in patients is establishing quantitative assays that distinguish between highly homologous proteins. The current study tested whether multiple members of two recently discovered ovarian cancer biomarker protein families, chloride intracellular channel (CLIC) proteins and tropomyosins (TPM), were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 47 publications
(57 reference statements)
5
66
1
Order By: Relevance
“…However, the existence of other TPM family members varied among the different types of cancers or studies (17)(18)(19). In the present study, TPM1 was significantly downregulated in most RCC tissues compared to that in the tumor adjacent normal renal tissues while TPM2-4 showed no significant expression differences in the RCC tissue samples.…”
Section: Discussioncontrasting
confidence: 50%
“…However, the existence of other TPM family members varied among the different types of cancers or studies (17)(18)(19). In the present study, TPM1 was significantly downregulated in most RCC tissues compared to that in the tumor adjacent normal renal tissues while TPM2-4 showed no significant expression differences in the RCC tissue samples.…”
Section: Discussioncontrasting
confidence: 50%
“…In support of this, several LMSS proteins have been reported previously as circulating biomarkers in cancer patients, correlating to presence of cancer or associating with poor clinical outcome. As such, serum CLIC4 levels were elevated in ovarian cancer patients compared with controls (Tang et al 2013), LCP1 was increased in the plasma of patients with kidney cancer (Tang et al 2013), and the plasma GDF15 levels were high in colorectal cancer patients and predicted poor survival (Wallin et al 2011;Mehta et al 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, TPM2 may be a biomarker candidate for CRC. Several early studies also showed that TPM2 was downregulated in human esophageal squamous cell carcinoma [34] and upregulated in ovarian cancer [35] and breast cancer [36]. TPM2 can be detected in the serum of ovarian cancer patients, and the TPM2 expression level is higher in the serum sample of ovarian cancer patients than in the serum sample of healthy volunteers [35].…”
Section: Discussionmentioning
confidence: 99%